Obtenção de nanocelulose de palha de cana-de-açúcar com diferentes teores de lignina residual - Almeida, Gabriela Fornaziero de (Universidade Federal de São Carlos, 2023)
Brazil stands out for its high production of sugarcane. This production generates a significant amount of byproducts, such as sugarcane straw. Due to its high cellulose content, converting straw into nanocellulose can be a promising alternative to add value to such a side-stream. Recent studies have shown that producing nanocellulose with residual lignin is a sustainable alternative to modify its surface properties. Residual lignin reduces the hydrophilicity of the nanocellulose, improves its compatibility with hydrophobic polymers and increases its thermal stability. Given the growing interest in the study of lignin-containing nanocellulose (L-NC) and the possibility of using sugarcane byproducts for this purpose, this work aimed to obtain L-NC from sugarcane straw with different residual lignin contents to investigate the effect of lignin on the thermal, morphological, surface, and structural properties of nanocellulose. The lignin content in the straws was varied by bleaching with chlorine dioxide under two conditions of reaction time and amount of bleaching chemicals. Three types of L-NC were produced using sulfuric acid hydrolysis from three biomass samples, namely: unbleached straw (U), mildly bleached straw (MB), and severely bleached straw (SB). The resulting lignin contents were 17.3 ± 0.3% for US, 14.7 ± 0.3% for MB, and 4.6 ± 0.8% for SB. Higher yields were observed for the L-NC obtained from bleached straws, which are purer in terms of cellulose. Atomic force microscopy confirmed the isolation of cellulose nanocrystals and nanofibers, regardless of the bleaching severity. Finally, lignin was found to increase the thermal stability of nanocellulose while reducing its crystallinity index, and colloidal stability. Its width and hydrophilicity did not vary significantly.
Production of nanocellulose from sugarcane straw bearing different contents of residual lignin
Keywords: Nanocelulose marrom; Nanocristal; Nanofibra; Lignina residual; Nanomateriais; Celulose; Palha de cana-de-açúcar; Resíduo agroindustrial; Brown nanocellulose; Nanocrystal; Nanofiber; Residual lignin; Nanomaterials; Cellulose; Sugarcane straw; Agri-food waste; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA